Artificial diet adjustments for brazilian strain of Hypothenemus hampei (Ferrari, 1867) (Coleoptera: Curculionidae) - Giraldo-Jaramillo, Marisol; Postali Parra, José Roberto (Coffee Science - ISSN 1984-3909, 2018)
A modified artificial diet based on the “Cenibroca diet” used in Colombia for mass rearing of Hypothenemus hampei, was compared with the natural diet presently used to rear this insect. The modified diet was cheaper than Portilla’s diet and did not affect insect fitness, developmental time, viability or sex ratio.